Emergy synthesis for aquaculture: A review on its constraints and potentials - David, Luiz H. [UNESP]; Pinho, Sara M. [UNESP]; Agostinho, Feni; Kimpara, Janaina Mitsue; Keesman, Karel J.; Garcia, Fabiana [UNESP] (Wiley, 2021)
The search for healthier protein sources and the growing demand for food by an increasing world population require aquaculture systems to not only be economically and technologically viable, but also sustainable. Among other methods, emergy synthesis is a powerful tool to assess the sustainability of production systems in a biophysical perspective. However, applications of emergy synthesis on aquaculture systems are seldomly found in the scientific literature. This work provides a literature review on emergy synthesis applied to aquaculture systems and discusses its constraints and potentials. The sixteen papers published between 2000-2020 support the adoption of polycultures more than monocultures and highlight the importance of feed (4–70%) in the total emergy required by aquaculture systems, which require efforts for natural food. Methodological aspects of emergy synthesis applied in aquaculture systems that deserve attention by developers and analysts to avoid mistakes and erroneous conclusions were identified and discussed, and we propose some ways to solve them. These aspects are mainly related to inaccurate unit emergy values for water and feed, dubious procedures in quantifying and classifying water as renewable or non-renewable resources, and the need to recognize the importance in accounting for ecosystem services and disservices. After overcoming these methodological inconsistencies, we foresee that emergy synthesis has potential political implications in supporting most sustainable aquaculture systems through economic (tax reduction and loans with reduced interests) and political (green labels) incentives. All these policies are important to achieve the ultimate goals of the United Nations’ Agenda 2030.
Keywords: aquaculture production; ecosystem services and disservices; feed; integrated systems; public policies; sustainability assessment